CGIAR Climate Impact Platform Collaborates with Juno Evidence Alliance to Inform Evidence Synthesis in Climate Change & Agri- Food Systems Research - Bosire, Caroline (2024)
The CGIAR Climate Impact Platform is collaborating with the Juno Evidence Alliance to inform high-quality evidence synthesis in the field of climate change & agri-food systems. Juno Evidence Alliance is supporting the Platform through the facilitation systematic review methods training workshops for CGIAR scientists and partners with trainings, facilitation of advanced training courses for senior scientists, and ongoing mentorship on scoping reviews, rapid reviews, and bibliometric reviews.